Cropland repurposing as a tool for water sustainability and just land transition in California: review and best practices - Fernandez-Bou, Angel Santiago; Rodriguez-Flores, Jose M.; Ortiz-Partida, J. Pablo; Fencl, Amanda; Classen-Rodriguez, Leticia M.; Yang, Vivian; Williams, Emily; Schull, Val Zayden; Dobbin, Kristin B.; Penny, Gopal; Escobedo Garcia, Nataly; Christian-Smith, Juliet; et al. (Frontiers in Water, 2025)
There is not enough water in California to support current water uses and preserve healthy environments. California aquifers have been chronically depleted over decades, causing household water insecurity, degrading groundwater-dependent ecosystems, affecting small and medium farmers, and inducing subsidence. The California government enacted the Sustainable Groundwater Management Act more than a decade ago to prevent declining aquifer levels to continue causing undesirable results, which has driven the necessity to reduce irrigated agriculture by about half million hectares. If this change is left to market forces alone, cropland retirement could disrupt local economies and vulnerable communities, increasing the levels of injustice for local residents and threatening farmer and farmworker livelihoods. However, when cropland repurposing is strategically organized and managed in collaboration among all the involved groups, it can enhance quality of life in agricultural disadvantaged communities, diversify regional economies, generate local socioeconomic opportunities, and improve environmental health while simultaneously fostering food and nutrition security and advancing water sustainability. In this study, we present a systems-level, coproduced Framework of best practices in cropland repurposing to achieve socioenvironmental and economic benefits for all. The Framework is informed and supported by peer-reviewed science, authors' first-hand experiences, and public engagement about the topic for several years. Our team includes scientists, community leaders, and other experts in cropland repurposing, socioenvironmental justice, agriculture, climate change, land trusts, disadvantaged communities, energy, nonprofit work, Indigenous knowledge, and ecosystems. The Framework includes guiding objectives, best practices, and implementation strategies to overcome co-occurring challenges. We conduct an extensive literature review of the current status quo to support the best practices identified in our Framework. This review and coproduced Framework aim to provide best practices for developing new solutions without causing new problems, while fully considering the impacts on all groups affected firsthand by cropland repurposing.